Calcium Modification Therapies in Contemporary Percutaneous Coronary Intervention - Zaidan, Mohammad; Alkhalil, Mohammad; Alaswad, Khaldoon (Current Cardiology Reviews, 2022)
Coronary Artery Calcification (CAC) has been known to be associated with worse Percutaneous Coronary Intervention (PCI) short- and long-term outcomes. Nowadays, with the increased prevalence of the risk factors leading to CAC in the population and also more PCI procedures done in older patients and with the growing number of higher-risk cases of Chronic Total Occlusion (CTO) PCI and PCI after Coronary Artery Bypass Grafting (CABG), severe cases of CAC are now encountered on a daily basis in the catheterization lab and remain a big challenge to the interventional community, making it crucial to identify cases of severe CAC and plan a CAC PCI modification strategy upfront. Improved CAC detection with intravascular imaging helped identify more of these severe CAC cases and predict response to therapy and stent expansion based on CAC distribution in the vessel. Multiple available therapies for CAC modification have evolved over the years. Familiarity with the specifics and special considerations and limitations of each of these tools are essential in the choice and application of these therapies when used in severe CAC treatment. In this review, we discuss CAC pathophysiology, modes of detection, and different available therapies for CAC modification.
Keywords: stent